Predominant Rab-GTPase amplicons contributing to oral squamous cell carcinoma progression to metastasis - Silva, Sabrina Daniela da; Marchi, Fabio Albuquerque [UNESP]; Xu, Bin; Bijian, Krikor; Alobaid, Faisal; Mlynarek, Alex; Rogatto, Silvia Regina [UNESP]; Hier, Michael; Kowalski, Luiz Paulo; Alaoui-Jamali, Moulay A. (Oncotarget, 2015)
Metastatic oral squamous cell carcinoma (OSCC) is frequently associated with recurrent gene abnormalities at specific chromosomal loci. Here, we utilized array comparative genomic hybridization and genome-wide screening of metastatic and non-metastatic tongue tumors to investigate genes potentially contributing to OSCC progression to metastasis. We identified predominant amplifications of chromosomal regions that encompass the RAB5, RAB7 and RAB11 genes (3p24-p22, 3q21.3 and 8p11-12, respectively) in metastatic OSCC. The expression of these Rab GTPases was confirmed by immunohistochemistry in OSCC tissues from a cohort of patients with a follow-up of 10 years. A significant overexpression of Rab5, Rab7 and Rab11 was observed in advanced OSCC cases and co-overexpression of these Rabs was predictive of poor survival (log-rank test, P = 0.006). We generated a Rab interaction network and identified central Rab interactions of relevance to metastasis signaling, including focal adhesion proteins. In preclinical models, mRNA and protein expression levels of these Rab members were elevated in a panel of invasive OSCC cell lines, and their down-regulation prevented cell invasion at least in part via inhibition of focal adhesion disassembly. In summary, our results provide insights into the cooperative role of Rab gene amplifications in OSCC progression and support their potential utility as prognostic markers and therapeutic approach for advanced OSCC.
Keywords: Acgh; Genomic; Metastasis; Oral squamous cell carcinoma; Rab gtpases